Assessment Quality of Nursing Care Provided to Neonates with Respiratory Distress Syndrome at Intensive Care Unit in AL- Nasiriyah City Hospitals - Qusay H. Mansi; Afifa R. Aziz (Kufa Journal for Nursing Sciences)
Objectives: this study aims to assess Demographic Characteristics like (age, level of nursing education and nurse's experience in the intensive care unit), and to assess quality of nursing care and to detect the association between the quality of nursing care with Demographic Characteristics like (age, level of nursing education and nurses experience in the intensive care unit). Methodology: A descriptive quantitative design is carried out at Intensive Care Unit in AL- Nasiriya City Hospitals include Bent Al-Huda Teaching Hospital, Muhammad AL-Mawsawi pediatric Hospital and Al-Hububi Teaching Hospital, the study period from 19 Dec, 2016 to 16 Feb, 2017. A non-probability (Purposive) of (100) nurses at intensive care unit to provide care for neonate with respiratory distress syndrome. To achieve the objective of the study the researcher has established the constructed questionnaire, which consists of two part 1: which include sociodemographic data form that consist of 8-itemsand part 2 include quality of nursing care that consist of three domains. Reliability of this determined by using Cronbach reliability rate (0.81), also through a pilot study and the validity through a panel of (18) experts. The data were described statistically and analyzed through use of the descriptive and inferential statistical analysis procedures. Results: The findings of the present study indicate that assessment quality of nursing care in neonatal respiratory distress syndrome for nurses at intensive care unit, since their relative sufficiency (75%) were under cutoff point (1.5), There was significant relationship between quality of nursing care and demographic characteristics like (age, level of nursing education and nurses experience in the intensive care unit by P value < 0.05). Recommendations: The study recommended to providing educational program for nurses for improving quality of nursing care of neonatal respiratory distress syndrome and Providing updating booklets, pamphlets and boosters for nurses to upgrading their knowledge about neonatal respiratory distress syndrome.